Scenographic Architecture in Games - Oliveira, Bárbara do Nascimento; Soares Filha, Anna Maria Vieira; Cavalcante, Morgana Maria Pitta Duarte (JRG Journal of Academic Studies, 2024)
The aim of this article is to analyze the intersection between architecture and scenography, with a specific focus on scenographic architecture in digital games. The research employs a theoretical-analytical and qualitative approach and was developed in two stages: an extensive bibliographic review and a detailed theoretical discussion on the subject. Observing the historical evolution of scenography, from the conceptualization of theater stages in ancient Greece to its approach and common practice in modern video games, it is evident that virtual scenography plays a fundamental role as a narrative and immersive element, enhancing players' experiences. Finally, this study highlights scenographic architecture as a powerful tool for creating interactive fictional worlds, offering the audience a unique engagement with the virtual space.